Recent Advances in Enantioselective Organocatalytic Reductionof C=N Bonds with Hantzsch Esters as the Hydride Source - WANG, ZHOUYU; JIANG, ZHENJU (Asian Journal of Chemistry, 2010)
Reduction of C=N bonds with metal-free chiral organocatalysts isan attractive approach to get optically active amines. This review focuseson the recent developments in enantioselective organocatalytic reductionof C=N bonds by Brønsted acids with Hantzsch esters as the hydridesource. The studies of several research groups such as Rueping, List,MacMillan, Antilla, You and Du are involved and the potential strengthsof the catalysts as well as the weaknesses are discussed.